Financial Literacy and Social Work Students: Knowledge is Power - Martie Gillen; Diane N Loeffler (Journal of Financial Therapy, 2012)
The continued economic turmoil makes it imperative for the profession of social work, specifically within academic programs, to teach students how to utilize their education, training and skills to promote social and economic justice and to create social change on multiple levels, in numerous setting, and with clients in diverse economic situations. In order to create curricular components that can help social workers to better practice with marginalized populations, we must first better understand what social work students do (or do not) know about financial literacy. The purpose of this exploratory study was to better understand the financial literacy of undergraduate and graduate social work students. Findings suggest that students are not gaining the skills they need to successfully navigate the complexities of the personal finance landscape. Further, it suggests that they will not be well equipped to help clients in this area. Social workers, especially those at the BASW level, work primarily in case management positions wherein they can be called upon to help clients in this area. We, in academia, must create opportunities for education to enhance student competency in this area.
Keywords: social work; financial therapy; financial counseling